Low auxin sensitivity of diageotropica tomato mutant alters nitrogen deficiency response - Dos Santos, Luiz C. N. [UNESP]; Gaion, Lucas A.; Prado, Renato M. [UNESP]; Barreto, Rafael F. [UNESP]; Carvalho, Rogério F. [UNESP] (FapUNIFESP (SciELO), 2020)
Plant responses to nitrogen supply are dependent on auxin signaling, but much still remains to be elucidated regarding N deficiency in tomato. Thus, the objective of this work was to evaluate how low auxin sensitivity regulates the responses of tomato plants to N deficiency. For this purpose, we used the tomato diageotropica mutant, with low auxin sensitivity, and a near isogenic line cv. Micro-Tom grown in nutrient solutions under absence and presence of nitrogen. Plant height, stem diameter, root and shoot dry mass, area and root density, number of lateral roots, leaf area, chlorophylls and carotenoids content, nitrogen accumulation and nitrogen use efficiency were evaluated. We observed a clear interaction between the tomato genotype and nitrogen. When the plants were grown with nitrogen, ‘Micro-Tom’ showed higher growth than the diageotropica mutant. Under nitrogen deficiency condition, the mutant showed improved growth, nitrogen use efficiency and higher contents of pigments. In general, the low sensitivity to auxin in diageotropica caused reduced growth in both shoot and root. However, the diageotropica tomato showed a positive regulation of the nitrogen use efficiency under nitrogen deficiency. In general, our data revealed that the reduced sensitivity to auxin increased the adaptive capacity to the nitrogen deficiency.
Keywords: Auxin; Cyclophilin protein; Plant hormone; Plant nutrition; Solanum lycop-ersicum L.